Pulmonary artery sarcoma with mediastinal metastasis: a case report - Cai, Jin; Nan, Bin; Liu, Fangbin; Ge, Yinghui; Guo, Zhiping; Kan, Xiaojing (Frontiers in Oncology, 2026)
We report a 67-year-old man presenting with a 9-month history of intermittent cough and chest pain. Dual-energy CT (DECT) demonstrated: (1) continuous filling defects extending from the main pulmonary artery through the right pulmonary artery into multiple segmental branches; (2) a middle mediastinal soft tissue mass closely related to the left pulmonary artery, left atrium, and left superior pulmonary vein, with spectral curve slope matching that of the intraluminal lesion in the pulmonary artery; (3) multiple irregular aneurysms in the left lower pulmonary artery; (4) cavitation in the right lung. Pulmonary artery biopsy confirmed undifferentiated pulmonary artery sarcoma. Pulmonary angiography revealed multiple left pulmonary artery aneurysms, and the right lung cavitation improved with antifungal therapy. This case demonstrates that pulmonary artery sarcoma can metastasize to the mediastinum, with metastatic lesions invading arteries and causing aneurysms. DECT plays a crucial role in diagnosis.